STRATEGY TO IMPROVE VILLAGE ECONOMY THROUGH SENTUL NGAHIJI BUMDES BY SENTUL VILLAGE GOVERNMENT - Iwan Dermawan Hanafi Gulo; Meltarini Meltarini; Baharuddin Thahir (Sean Institute, 2023)
BUMDes Sentul Ngahiji is one of the Village-Owned Enterprises owned by Sentul Village and has the potential to contribute income to the village because of its strategic position. This study aims to determine the strategy to improve the village economy through BUMDES Sentul Ngahiji by the Sentul Village Government and the supporting and inhibiting factors to improve the village economy through BUMDES Sentul Ngahiji. The phenomenon that occurs is that BUMDes administrators have yet to be active in carrying out their main duties and functions according to applicable regulations. The research method used is a qualitative descriptive with data collection techniques through observation, interviews and documentation. In this study the author used ASOCA Analysis Method. The research results show that the management of Sentul Ngahiji BUMDes is less than optimal because the operational implementing human resources have yet to be given a decree so that the main tasks and functions are less than optimal in terms of accountability. For this reason, it is necessary to elect or recruit new BUMDes management. To realize effectiveness and openness in the management of BUMDes.